The distribution of psychosis, ICD-11 PTSD and complex PTSD symptoms among a trauma-exposed UK general population sample. Issue 3 (3rd July 2019) - Frost, Rachel; Louison Vang, Maria; Karatzias, Thanos; Hyland, Philip; Shevlin, Mark
ABSTRACT: Background : Co-occurrence of psychosis and posttraumatic stress disorder (PTSD) symptoms has been demonstrated, but the ICD-11 marks a significant divergence in the formulation of PTSD with a focus on the core symptoms and the addition of complex PTSD (CPTSD). Objective : To evaluate the distribution of psychosis and traumatic stress symptoms using the ICD-11 conceptualisation of PTSD and CPTSD. Method : A latent class analysis was conducted on psychosis symptoms, PTSD and CPTSD among a random adult sample from the UK general population with a history of traumatic events (N = 1, 051). Results : Six classes were identified; a low-symptom class, a PTSD-class, a CPTSD-class, a class characterized by disturbances in self-organization alone as well as two classes characterized by CPTSD and various levels of psychosis symptom endorsement. Cumulative childhood adversity predicted membership of the PTSD, CPTSD and comorbid classes in a dose-response manner with the strongest effects observed for classes characterised by comorbid symptoms. Conclusion : The present study confirms the co-occurrence of psychosis symptoms and ICD-11 PTSD and CPTSD. Psychosis symptoms did not emerge in isolation from traumatic stress symptoms, underpinning the need for a greater recognition of psychosis symptoms as part of the broader clinical picture among trauma-exposed populations.